Insights into bioactive constituents of onion (Allium cepa L.) waste: a comparative metabolomics study enhanced by chemometric tools - Mariam M. Elattar; Hala M. Hammoda; Doaa A. Ghareeb; Shaymaa A. Abdulmalek; Fatma. A. Abdelrahim; Inas A. K. Seif; Hend M. Dawood; Reham S. Darwish (BMC, 2024)
Abstract Background Onion waste was reported to be a valuable source of bioactive constituents with potential health-promoting benefits. This sparked a surge of interest among scientists for its valorization. This study aims to investigate the chemical profiles of peel and root extracts of four onion cultivars (red, copper-yellow, golden yellow and white onions) and evaluate their erectogenic and anti-inflammatory potentials. Methods UPLC-QqQ-MS/MS analysis and chemometric tools were utilized to determine the chemical profiles of onion peel and root extracts. The erectogenic potential of the extracts was evaluated using the PDE-5 inhibitory assay, while their anti-inflammatory activity was determined by identifying their downregulating effect on the gene expression of IL-6, IL-1β, IFN-γ, and TNF-α in LPS-stimulated WBCs. Results A total of 103 metabolites of diverse chemical classes were identified, with the most abundant being flavonoids. The organ's influence on the chemical profiles of the samples outweighed the influence of the cultivar, as evidenced by the close clustering of samples from the same organ compared to the distinct separation of root and peel samples from the same cultivar. Furthermore, the tested extracts demonstrated promising PDE-5 and anti-inflammatory potentials and effectively suppressed the upregulation of pro-inflammatory markers in LPS-stimulated WBCs. The anti-inflammatory activities exerted by peel samples surpassed those of root samples, highlighting the importance of selecting the appropriate organ to maximize activity. The main metabolites correlated with PDE-5 inhibition were cyanidin 3-O-(malonyl-acetyl)-glucoside and quercetin dimer hexoside, while those correlated with IL-1β inhibition were γ-glutamyl-methionine sulfoxide, γ-glutamyl glutamine, sativanone, and stearic acid. Taxifolin, 3'-hydroxymelanettin, and oleic acid were highly correlated with IL-6 downregulation, while quercetin 4'-O-glucoside, isorhamnetin 4'-O-glucoside, and p-coumaroyl glycolic acid showed the highest correlation to IFN-γ and TNF-α inhibition. Conclusion This study provides a fresh perspective on onion waste as a valuable source of bioactive constituents that could serve as the cornerstone for developing new, effective anti-PDE-5 and anti-inflammatory drug candidates.